Inland fish consumption patterns of local fishing community from ex-mining lakes in Sg. Galah, Kg. Gajah, Malaysia - Abdul Azhar, Fathin Shakira; Zainuddin, Mohamad Faiz; Mohamat Yusuff, Ferdius @ Ferdaus; Ong, Meng Chuan; Zulkeflee, Zufarzaana (Malaysian Society of Applied Biology, 2024)
Evaluating the potential risks upon fish consumption requires an understanding of the different patterns of fish intake by consumers. The objectives of the study were (i) to acquire information pertaining to the fish consumption level and frequency, and (ii) to investigate the relationships between respondents' preferences and their demographic and socioeconomic characteristics. A cross-sectional survey, through non-probabilistic random sampling was carried out in Sg. Galah, Kg. Gajah, Malaysia between November 2021, and December 2022 to take a look at the fish consumption patterns of the inland fishing community. This study covered 155 respondents, with a mean age of 40 years old. Male participants made up 76.8% of the sample, while female participants made up 23.2%. The findings showed that the following fish species were most consumed from the former mining lake, in decreasing order: Helostoma temminckii (Kissing gourami/Temakang), Pangasianodon hypophthalmus (Patin hitam), Labeo rohita (Rohu), Hypophthalmichthys nobilis (Bighead carp/Tongsan), Barbonymus schwanefeldii (River barb/Lampam), and Leptobarbus rubripinna (Sultan barb/Jelawat). The vast majority of respondents said that they eat fish of any size, regardless of species. There was no significant correlation between respondents' individual and family income, career, marital status, and educational level with their intake of fish. The information gathered will be the basis for the assessment of health risks associated with consuming inland fish originated from ex-mining lakes that may be contaminated with heavy metals.